Biomonitoring of Zn pollution by using Leaves, Stems and Roots of a Medicinal Plant Centella Asiatica - C. K. Yap; Ong G. H. (International Journal of Advances in Applied Sciences, 2014)
In this study, three parts (leaves, stems and roots) of Centella asiatica and surface soils were collected from 11 geographical sampling sites in Peninsular Malaysia. Ranges of Zn concentrations (µg/g dw) in soil was 102.70-826.11 while 81.16-198.56 for leaves, 56.27-146.93 for stems and 95.72-285.00 for roots. In C. asiatica, Zn accumulation was found the highest in roots followed by leaves and stems. Correlation analysis based on Zn concentrations between the three parts of plants and soils were found to be significantly (P< 0.05) correlated (root-soil, R= 0.973; leaves-soils, R= 0.955; stem-soils, R= 0.952). For the transplantation study, three sites were selected as unpolluted (UPM), semi-polluted (Balakong) and polluted sites (Sg. Juru). Based on transplantation study under experimental field and laboratory conditions, Zn concentrations in the leaves, stems and roots of C. asiatica were significantly (P< 0.05) higher after three weeks. The Zn accumulation was the highest in Sg. Juru, followed by Balakong and UPM which were in accordance with the Zn contamination levels in the soils. Thus, these experimental findings confirmed that leaves, stems and roots can reflect the Zn levels in the soils where C. asiatica were found. After three weeks of back transplantation to clean soils, the Zn levels in the three parts were still higher than the initial Zn level even though elimination occurred. In conclusion, all the above findings indicated that the leaves, stems and roots of asiatica are good biomonitors of Zn pollution.